PSA levels, PSA doubling time, Gleason score and prior therapy cannot predict measured uptake of [68Ga]PSMA-HBED-CC lesion uptake in recurrent/metastatic prostate cancer - Verburg, Frederik A.; Pfister, David; Drude, Natascha I.; Mottaghy, Felix M.; Behrendt, Florian F. (Nuklearmedizin - NuclearMedicine, 2017)
Aim: To assess whether clinical prostate cancer (PCA) related factors and therapy status can predict the degree of tracer uptake on [68Ga]PSMA-HBED-CC PET/CT.Materials & methods: We retrospectively studied 124 patients with recurrent an/or metastatic PCA who underwent [68Ga]PSMAHBED-CC PET/CT. The maximum standardized uptake value (SUVmax) was determined in the prostate bed as well as in three size categories (≤ 5 mm, > 5–15 mm, > 15 mm) in pelvic lymph node, extrapelvic lymph node, bone and visceral metastases.Results: Significant positive correlations between lesion size and SUVmax were found in pelvic lymph node metastases > 5 -≤15 mm (Spearmans rho = 0.502, p = 0.002) as well as in extrapelvic lymph node metastases5 mm (rho = 0.314, p = 0.033) and > 5 ≤-15 mm (rho = 0.614, p < 0.001). SUVmax tended to be higher in the largest diameter category in each anatomic station than in the middle and lower categories. We were unable to find evidence for a relationship between SUVmax and PSA, PSAdt, Gleason score, androgen deprivation therapy, radiation therapy or chemotherapy status.Conclusion: Measured tracer uptake in [68Ga]PSMA-HBED-CC PET/CT in patients with recurrent/metastasized prostate cancer is significantly influenced by lesion size as a result of partial volume effects in the very small lesions. Clinical indicators of aggressive prostate cancer behaviour such as PSA levels, PSA doubling time or the Gleason score of the primary tumour, as well as the androgen deprivation therapy, radiation therapy or chemotherapy status are not related to measured tracer uptake.Ziel: Beantwortung der Frage ob klinisch bestimmbare Faktoren und Therapiestatus bei Prostatakarzinom (PCA) eine Vorhersage zur Traceranreicherung in [68Ga]PSMA-HBED-CC PET/CT liefern können.Material & Methoden: 124 Patienten mit rezidiviertem und/oder metastasiertem PCA die [68Ga]PSMA-HBED-CC PET/CT untergingen, wurden retrospektiv untersucht. Der maximum Standardized Uptake Value (SUVmax) wurde in der Prostataloge gemessen sowie in drei Größen-Kategorien ( 5 mm, > 5–15 mm, > 15 mm) in Metastasen in den pelvinen Lymphknoten-, extrapelvinen Lymphknoten-, Knochen- und viszeralen Metastasen. Ergebnisse: Signifikant positive Korrelationen zwischen Läsionsgröße und SUVmax wurden in pelvinen Lymphknotenmetastasen > 5 -≤15 mm (Spearmans rho = 0.502, p = 0.002), extrapelvinen Lymphknotenmetastasen5 mm (rho = 0.314, p = 0.033) und > 5 -≤15 mm (rho = 0.614, p < 0.001) gefunden. Für jede anatomische Lokalisation wurde ein höherer Wert SUVmax innerhalb der größten Kategorie verglichen zu mittleren und kleinsten Kategorie gefunden.
Keywords: PSA; PSA doubling time; Gleason score; prostate cancer; [68Ga]PSMA-HBED-CC PET/CT